Kalium Sebagai Solusi Hipertensi - Gerardin Ranind Kirana; Reny Nugraheni; Vivien Dwi Purnamasari; Forman Novrindo Sidjabat (PaKMas: Jurnal Pengabdian Kepada Masyarakat, 2024)
Hypertension is one of the degenerative diseases, where the number of diseases will continue to increase as a person ages. Hypertension itself can cause several complications such as CHD, stroke, kidney failure, diabetes mellitus, and even hypertension can be a factor causing sudden death because sometimes someone who suffers from hypertension does not experience any symptoms. The purpose of community service entitled "Potassium as a Solution for Hypertension" is to increase public knowledge about hypertension and how to prevent it. The community service techniques used are lecture methods on hypertension and how to prevent it, as well as direct practice of several ways to prevent hypertension in the form of hypertension exercises for the elderly and making cucumber juice containing potassium, magnesium, and vitamin C, which can lower blood pressure. The questions for Pre-Test and Post-Test were modified based on the material discussed and consisted of 5 true or false questions. The community service activities carried out in RT 07 RW 02 Kelurahan Singonegaran, Kota Kediri, succeeded in increasing public knowledge about hypertension and how to prevent it. The results of the activities showed that the average correct answer in the pre-test was 42.8%, increasing to 89.2% in the post-test. Maintaining a diet, diligently doing physical activities, and also drinking cucumber juice which contains substances to lower blood pressure, is highly recommended for residents of RT 07 RW 02 Kelurahan Singonegaran, Kota Kediri, to be done regularly every day.